Agency law in commercial practice - Busch, Danny; Macgregor, Laura; Watts, Peter, 1942- (Oxford : Oxford University Press, 2016)
An essential guide to agency law, exploring its problems and application in commercial practice.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 2, 2016).
Keywords: Agency (Law); Commercial agents -- Legal status, laws, etc; Law; Laws of specific jurisdictions & specific areas of law